Recent Advances in Combining Photo- and N-Heterocycle Nitrenium Catalysis - Li, Xiang; Tu, Yong-Liang; Chen, Xiang-Yu (Synthesis, 2024)
N-Heterocyclic nitreniums (NHNs) are isoelectronic and isostructural analogues of N-heterocyclic carbenes (NHCs). Unlike NHCs, NHNs are much less developed. While a comprehensive understanding of NHN reactivity remains elusive, recent advancements have demonstrated their utility as Lewis acid catalysts, photoreductants, and photooxidants, leading to several reaction patterns. In this short review, we focus on the applications of NHNs in photoredox reactions. We also discuss the mechanisms behind these transformations and outline future research directions.1 Introduction2 Application of N-Heterocyclic Nitreniums as Photoreductants3 Application of N-Heterocyclic Nitreniums to Facilitate Photohomolysis4 Application of N-Heterocyclic Nitreniums as Photooxidants5 Conclusion
Keywords: N-heterocyclic nitreniums; photoreductant; π-hole interaction; photooxidant; charge-transfer complex